2022
DOI: 10.3390/ijerph19148864
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses at 15 Minutes of Recovery after a Session of Functional Fitness Training in Well-Trained Athletes

Abstract: Background: the aim of this study was to analyse muscle fatigue and metabolic stress at 15 min of recovery after performing two independent sessions of functional fitness training (FFT): a session of strength functional fitness training (FFTstrength) and a session of endurance functional fitness training (FFTendurance). Methods: eighteen well-trained men conducted two protocols, separated by one week of rest: FFTstrength (3 sets of 21, 15 and 9 repetitions of Thruster with bar + Pull ups) and FFTendurance (3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Comparing these results with those of another study that measured the physiological responses of an FFT protocol up to 15 min of rest, it was observed that MPV at 1 m·s −1 was not recovered only in the military press test of FFTstrength [ 18 ]. However, in the fatigue test at 1 m·s −1 in squat of the FFTstrength and in the fatigue tests in military press and squat of FFTendurance, the pre-exercise values were recovered, despite obtaining values of ≈13 mmol·L −1 after 15 min of rest [ 18 ]. The high values of blood lactate compared to those obtained in this protocol (≈4 mmol·L −1 ) may be due to the different nature of the exercises and the time used to execute each exercise.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Comparing these results with those of another study that measured the physiological responses of an FFT protocol up to 15 min of rest, it was observed that MPV at 1 m·s −1 was not recovered only in the military press test of FFTstrength [ 18 ]. However, in the fatigue test at 1 m·s −1 in squat of the FFTstrength and in the fatigue tests in military press and squat of FFTendurance, the pre-exercise values were recovered, despite obtaining values of ≈13 mmol·L −1 after 15 min of rest [ 18 ]. The high values of blood lactate compared to those obtained in this protocol (≈4 mmol·L −1 ) may be due to the different nature of the exercises and the time used to execute each exercise.…”
Section: Discussionmentioning
confidence: 65%
“…However, few studies have measured the time that VL can be maintained or the moment at which the pre-exercise velocity values are recovered within the same training session. In a recent study, Maté Muñoz et al (2022) [ 18 ] measured neuromuscular fatigue in an endurance session of functional fitness training (FFTendurance) and in a strength session of functional fitness training (FFTstrength) through VL, reporting that this velocity was recovered after 15 min of rest. Although the velocity values of FFTendurance were recovered after 15 min of rest, in the FFTstrength session, velocity was only recovered in the 1 m·s −1 tests in squat, whereas velocity in the 1 m·s −1 tests in military press exercise decreased by 7%.…”
Section: Introductionmentioning
confidence: 99%
“…A progressive load test of BP to 1RM (1RM test) was performed based on the warm-up and the execution of the exercise protocol from previous studies [ 36 , 40 , 41 ], and we obtained the load-to-velocity ratio of each individual.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, although these earlier studies associate the improvements in performance with a greater capacity to recover between sets, a few studies have measured the recovery period after performing an intense exercise protocol. Recent studies have measured recovery at 15 min after a multiple-set exercise protocol with bench pressing [ 35 ] or a high-interval functional training protocol [ 36 ], with the aim of determining the recovery time required to perform another exercise protocol in the same session, reaching levels of execution velocity that are similar to those that were obtained in the first protocol, in order to reduce the residual fatigue and increase the performance capacity. In this sense, it would be interesting to know whether creatine supplementation can help people to recover the initial strength levels after performing an exercise protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Previous HIFT research demonstrates the necessity for balanced performance testing that is accessible to HIFT novices [ 34 ]. Moreover, previous HIFT research has used a single familiarization session for experienced participants prior to testing [ 35 ]. Considering HIFT’s physical health benefits, its ability to increase anticipatory anxiety, and its growing popularity, further research may help elucidate the relationship between anxiety, familiarization, and performance and establish an appropriate performance testing protocol for HIFT novices.…”
Section: Introductionmentioning
confidence: 99%